PROPUESTA TECNICA Y ECONOMICA DEL POT - -CEO-, Centro de Estudios de Opinión (La Sociología en sus Escenarios, 2009)
Abstract. This text tries to serve as frame for the agreement and socialization of the metropolitan directives of territorial ordering: Some recommendations according to the adjustments proposed by the municipalities in the revision of the plans of territorial ordering appear. Resumen. Este texto pretende servir de marco para la concertación y socialización de las directrices metropolitanas de ordenamiento territorial y ajustes propuestos por los municipios en la revisión de los planes de ordenamiento territorial.